0273 The Association Of Delta Activity At Sleep Onset And Delta Power With Cognition In Community-dwelling Older Adults. (27th April 2018) - Kawai, M; Schneider, L; O'Hara, R
Abstract: Introduction: Delta activity at sleep onset (DASO) is reported in older adults and our group has found DASO is associated with better cognition. However, whether DASO reflects delta power during sleep in older adults is unclear. Delta power during sleep in older adults may be indicative of 1) normal slow wave sleep, 2) pathological slow EEG, or 3) bursts of delta activity. In this study, we examined whether DASO is associated with delta power in sleep, and whether similar to our previous finding, delta power is associated with improved information-processing speed and attention. Methods: 153 community-dwelling older adults (83 females, 70 males) had polysomnography (PSG) and comprehensive cognitive assessment that included information-processing speed and attention. DASO was defined as sequences of rhythmic delta activity in awake/sleep transition. The sleepdata.org SpectralTrainFig MATLAB app calculated spectral power for each epoch. Delta power in DASO (+) and (-) group was compared. In exploratory analyses, we examined association of delta power with global cognition; delayed verbal memory; verbal naming; and visuospatial ability. Results: Mean age was 71.3 ± 0.6 years. DASO was present in 19.6%. No statistically significant differences were observed in delta power between DASO (+) and (-) group. Further, delta power was not associated with information-processing speed and attention. However, exploratory analyses found higher delta power in N1, NREM, and sleep to be associated with worse verbal naming (p=0.021, 0.027, 0.023, respectively) and delta in N1 with worse global cognition (p=0.032). Conclusion: Contrary to our hypotheses we observed no association between delta power and DASO. Further, increased delta power was not associated with better cognitive function on any cognitive measure. However, increased levels of delta power were associated with poorer verbal naming and global cognitive function. Our findings suggest that DASO is a parameter that is independent of delta power in sleep EEG, and that presence of DASO may represent a different sleep phenotype than that captured by delta power, with respect to the impact of sleep on cognitive functioning in older adults Support (If Any):